2014
DOI: 10.1371/journal.pone.0112456
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effect of Inhibitor Resistant S130G Mutant on Physico-Chemical Properties of SHV Type Beta-Lactamase: A Molecular Dynamics Study

Abstract: Bacterial resistance is a serious threat to human health. The production of β-lactamase, which inactivates β-lactams is most common cause of resistance to the β-lactam antibiotics. The Class A enzymes are most frequently encountered among the four β-lactamases in the clinic isolates. Mutations in class A β-lactamases play a crucial role in substrate and inhibitor specificity. SHV and TEM type are known to be most common class A β-lactamases. In the present study, we have analyzed the effect of inhibitor resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 38 publications
1
34
0
1
Order By: Relevance
“…We also examined the radius of gyration and solvent accessibility of surface area analysis to determine that how the unfolding of the mutant protein structure reduces the surface area solubility and how the protein activity is reduced. Higher the Rg value indicates lower the stability [40]. We observed that native structure has less Rg range as compare to the mutants which proved that both mutations Y127H and G334A decrease the stability of protein and hence reduce the protein functionality.…”
Section: Discussionmentioning
confidence: 58%
“…We also examined the radius of gyration and solvent accessibility of surface area analysis to determine that how the unfolding of the mutant protein structure reduces the surface area solubility and how the protein activity is reduced. Higher the Rg value indicates lower the stability [40]. We observed that native structure has less Rg range as compare to the mutants which proved that both mutations Y127H and G334A decrease the stability of protein and hence reduce the protein functionality.…”
Section: Discussionmentioning
confidence: 58%
“…The key signaling proteins PI3K, AKT, and mTOR are used in the current study for designing inhibitors as anticancer agents. Various computational drug‐design approaches, including molecular docking and dynamic simulation, have been successfully used for the identification of better drug candidates . The set of compounds used for screening against the 3 proteins includes naphthoquinones or naphthoquinone analogs.…”
Section: Introductionmentioning
confidence: 99%
“…V‐rescale temperature coupling and Parrinello‐Rahman pressure coupling were used to keep the system in a stable environment (300 k, 1 bar), and the coupling constants were set to 0.1 and 2.0 ps for temperature and pressure, respectively . The Partial Mesh Ewald (PME) algorithm . was employed for electrostatic and Van der Waals interactions; cut‐off distance for the short‐range VdW (rvdw) was set to 1.4 nm, where Coulomb cut‐off (r coulomb) and a neighbor list (rlist) were fixed at 0.9 nm.…”
Section: Methodsmentioning
confidence: 99%